On the measurement of a multidimensional concept of structural similarity - Crespo, N.; Simões, N. (Economics Letters, 2012)
The measurement of similarity and convergence of trade structures is usually based on indicators comparing the weight of each sector in total exports such as, for example, the Krugman specialization index. We propose a broader concept of structural similarity, incorporating two additional dimensions, and suggest indicators that include these new dimensions.